Akibat Hukum Pembatalan Perkawinan Terhadap Status Anak Dikaitkan dengan Kedudukannya dalam Mewaris (Contoh Kasus Putusan Kasasi Nomor 450 K/Pdt/2022) - Sugiarto, Febyola Berlyani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Marriages that have taken place and even one of the partners has passed away, in fact, can still be submitted for annulment of marriage from the family where this will affect the status of the child in occupying it as heir. This study aims to analyze the status of children due to the annulment of marriages based on Cassation Decision Number 450 K/Pdt/2022 and the inheritance rights of children which have an impact on the annulment of marriages based on the Civil Inheritance System in Indonesia. The problem studied is the status of children due to the cancellation of marriages based on Cassation Decision Number 450 K/Pdt/2022 and the inheritance rights of children which have the impact of canceling marriages based on the Civil Inheritance System in Indonesia. The research used is in the form of juridical-normative. In addition, this research is descriptive analytical. The type of data used is secondary data. The data collection tool used is document study with the technique used is qualitative. The results of this study indicate that the status of children who have been born from the (annulled) marriage, then as explained in the provisions of Article 28 paragraph (2) of the Marriage Law that the cancellation of marriage does not apply retroactively to children born from said marriage where the child is still considered as a legitimate child and the parents still have obligations to the child until the child can stand alone even though the marriage of the parents has been annulled. Furthermore, with regard to the inheritance rights of children affected by the cancellation of marriages, referring to Article 28 paragraph (2) of the Marriage Law, the child is still said to be a legitimate child so that he still has his position as an heir.Marriages that have taken place and even one of the partners has passed away, in fact, can still be submitted for annulment of marriage from the family where this will affect the status of the child in occupying it as heir. This study aims to analyze the status of children due to the annulment of marriages based on Cassation Decision Number 450 K/Pdt/2022 and the inheritance rights of children which have an impact on the annulment of marriages based on the Civil Inheritance System in Indonesia. The problem studied is the status of children due to the cancellation of marriages based on Cassation Decision Number 450 K/Pdt/2022 and the inheritance rights of children which have the impact of canceling marriages based on the Civil Inheritance System in Indonesia. The research used is in the form of juridical-normative. In addition, this research is descriptive analytical. The type of data used is secondary data. The data collection tool used is document study with the technique used is qualitative. The results of this study indicate that the status of children who have been born from the (annulled) marriage, then as explained in the provisions of Article 28 paragraph (2) of the Marriage Law that the cancellation of marriage does not apply retroactively to children born from said marriage where the child is still considered as a legitimate child and the parents still have obligations to the child until the child can stand alone even though the marriage of the parents has been annulled. Furthermore, with regard to the inheritance rights of children affected by the cancellation of marriages, referring to Article 28 paragraph (2) of the Marriage Law, the child is still said to be a legitimate child so that he still has his position as an heir.